UMUR DAN PEKERJAAN IBU TERHADAP PEMILIHAN KONTRASEPSI IUD - Arimina Hartati Pontoh (Akademi Kebidanan Griya Husada Surabaya, 2017)
The Family Planning Program continues to be pursued by the government to reduce the rate of population growth in order to create the welfare of the Indonesian population. In choosing contraception it is influenced by several factors, and in the selection of IUDs it can be influenced by age and occupational factors. From the data on the achievement of IUD selection at Sawahan Health Center Surabaya, the period January-June 2017 experienced fluctuations from year to year, namely 2014 amounting to 9.14%, 2015 amounting to 2.20% and 2016 amounting to 8.97%. The selection of the IUD was less than PPM (9.34%). So the research aims to find out the description of the age and work of mothers on the selection of IUDs in the Sawahan Health Center Surabaya in the period January-June 2017 Method: This study uses a descriptive method. The population is all family planning acceptors with sampling taken on a non-probability sampling and the sample used is a saturated sample which is the total population into a sample of 116 people. As an instrument of research, secondary data is used, then the data is processed with a frequency table and cross tabulation. Results: The results of the study found that family planning acceptors were mostly 20-35 years old with 68 people (58.62%), 99 unemployed (85.34%), the majority of acceptors did not choose an IUD of 101 people (87.07%). The results of cross tabulation found that family planning acceptors aged 20-35 did not choose 60 IUDs (88.24%) compared to <20 years old as many as 2 people (33.33%) chose IUDs and those who did not work did not choose 90 IUDs. people (90.91%) compared to working as many as 6 people (35.29%) chose an IUD. Discussion: It can be concluded that with age and low income it will affect family planning acceptors in the selection of IUDs. Therefore, for prospective acceptors to choose contraception according to their age and income, IEC is carried out, counseling, approaches and cross-sectoral cooperation to hold a KB safari.